The Development of Nursing Model for Preventing Critical Conditions in Neonates with Respiratory Distress, Sakon Nakhon Hospital - Waraasawapati, Wiraporn; Tuanyee, Sriamporn; Pakdeechot, Sasithorn; Tipamom, Wanpen (Journal of The Royal Thai Army Nurses, 2023)
The objectives of this research and development were to develop and evaluate a Nursing Model for Preventing Critical Conditions in Neonates with Respiratory Distress. The Mahjoubi’s research methodology was 6 steps and conducted during October 2022 to May 2023.The samples consisted of 4 executives, 34 registered nurses, 296 neonates and 148 caregivers. The research tools were composed of the Nursing Model for Preventing Critical Conditions in Neonates with Respiratory Distress, the nursing group discussion guideline and the satisfaction assessment form. The data were analyzed using group content, mean, percentile, t-test and Chi-square test The results revealed that 1) the Nursing Model for Neonates with Respiratory Distress consisted of 4 major components: (1) 4-phase nursing methods to prevent critical conditions being newborns-2 hours puerperium period, 2-6 hours old puerperium period, 6-hour puerperium period and distribution for in-home caring phase, (2) 7 aspects of nursing competency assessment, (3) enhancement of the skills and abilities of caregivers, and (4) the nursing clinical supervision. 2) The results of the developed Nursing Model found that the incident rate of unanticipated worsen conditions and unplanned ICU transfer were significantly lower than before implementing the model, and the specific competency showed significantly higher than before implementing the model (P<.05).